Modelling lipid biosynthesis pathways of oil palm by boolean and graphical approaches - Quek, Emily Ming Poh; Purutcuoglu, Vilda; Sambanthamurthi, Ravigadevi; WilhelmWeber, Gerhard (IEEE, 2011)
The mathematical modelling provides an alternative way for the interpretation and prediction of cellular metabolisms. This study delves into the modelling of lipid biosynthesis pathway and the primary metabolism in the fruit of the oil palm (Elaeis guineensis). Two different data are used for the analysis. In the first dataset, the distribution of carbon flux into the major classes of lipids, i.e., triacylglycerols, diacylglycerols, monoacylglycerols, phospholipids, and free fatty acids, is investigated using radioactive isotope. Then, the model of carbon flux is constructed based on the Boolean approach. On the other hand in the second dataset, the graphical methods are implemented to construct a model for the lipid contents of the developing oil palm mesocarp based on the major lipid metabolites of this system as listed previously. Moreover, the generated models are analysed for the control structure depending on the relative ranking of degree for each lipid class in the pathway. The results demonstrate the ability of the models to predict the site of control in this biosynthetic system. Furthermore, the analyses of the networks of lipids do not only reveal underlying interactions between the major classes of lipids but also the response of these networks towards changing environments.